FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN DI PEMERINTAH KABUPATEN KLATEN - Della Oktavia; Titiek Puji Astuti; Yunus Harjito (Accounting Global Journal, 2020)
This Study aims to examine the effect of Distributive Justice, Procedural Justice, Internal Control, Regulatioin Enforcement, Organizational Commitment, and Organizational Culture on Fraud at Klaten Regency Government. Type of research in this study is quantitative research. The samples in this study using saturation sampling/census. The samples in this study were Structural Functionary which involved with managing regional budget of OAP (Organization of Area Peripheral) Klaten Regency of 16 office and 4 governing corporation at Klaten Regency Government. The analysis data of this research uses a multiple regression test to test hypothesis. The result of analysis data in this research shows that the Distributive Justice, Internal Control, Regulation Enforcement and Organizational Commitment have a negative effect on Fraud while the Procedural Justice and Organizational Culture does not effect on Fraud